Panama : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1999)
This paper provides background information to the IMF staff report for the 1998 Article IV Consultation discussions with Panama. It focuses on areas of interest in Panama's medium-term economic strategy, and gives a broad overview of economic developments with emphasis on 1997. It updates information on important areas of economic activity: the structure and reform of the financial sector; reversion of the Canal Zone areas to Panama; and analysis of key elements of the economic reform program since 1994, including trade reform and other measures to foster competitiveness and competition.